RANCANG BANGUN SISTEM LAYANAN INFORMASI MEMBERSHIP FITNESS CENTER BERBASIS INTERNET OF THINGS - Al Ashar, Muhamad Haqim; Zainuri, Akhmad; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
The significant growth of the fitness center industry in recent years reflects a change in lifestyle where people are increasingly concerned about health and fitness. Although modern fitness centers offer a variety of exercise programs and complete facilities, they face major challenges related to low service quality. The main issues include ineffective management, poor service, and inadequate security for members' valuables. Proposed solutions to address these problems include the development of a membership information service system based on the Internet of Things (IoT) and WhatsApp chatbots. IoT technology allows real-time monitoring of visitor numbers, while RFID enhances locker security. WhatsApp chatbots provide real-time information about visitor density and membership status. Test results show that Google Spreadsheets can be used as an adequate alternative database, and the ESP32 microcontroller meets the system's functionality needs. The implementation of this technology is expected to automate several tasks in fitness centers, reduce the need for human resources, and improve operational efficiency and customer satisfaction. Thus, fitness centers can make a positive contribution to public health. Keywords: Internet of Things, Fitness Center, Membership, Microcontroller, ESP32, Database, Chatbot, Google SpreadSheets, Google App Scripts